Advances in condensed matter optics - Chen, Liangyao (Physics Professor); Dai, Ning, 1959-; Jiang, Xunya, 1967-; Zhao, Haibin (Physics Professor); Jin, Kuijuan (Physics Professor); Liu, Hui (Physics Professor) (Walter de Gruyter GmbH & Co. KG, 2015)
This book describes some of the more recent progresses and developments in the study of condensed matter optics in both theoretic and experimental fields. It will help readers, especially graduate students and scientists who are studying and working in the nano-photonic field, to understand more deeply the characteristics of light waves propagated in nano-structure-based materials with potential applications in the future.
Keywords: Condensed matter -- Optical properties.; Optics.; Metamaterials.; elektronické knihy; electronic books